Effect of Local Microorganism Utilization to Increase Productivity of Javanese Turmeric (Curcuma xanthorriza Roxb.) - Faiza, Lucky Lia; Arifin, Poppy F.; Nurcholis, Waras; Ridwan, Taufik; Darusman, Latifah K; Susilowidodo, Raphael Aswin; Wisastra, Rosalina (Jurnal Jamu Indonesia, 2018)
The quality of javanese turmeric as one of the most widely use herb in Indonesian traditional medicine, is often ignored and unoptimized. Therefore, research on Javanese turmeric cultivation become critical to be performed.One of crucial aspect is sufficiency of water and nutrients to increase rhizome productivity during vegetative period. Therefore, fertilization plays an important role in increasing soil macronutrients content and ultimately enhance Javanese turmeric’s quality.The aim of this research is to determine the potential of addition local microorganism (LMO) solution as an organic fertilizer on rhizome production and bioactive content of Javanese Turmeric . The research on LMO application for Javanese turmeric plantation was conducted at Soho Center of Excellence in Herbal Research (SCEHR). LMO was made by utilizing local waste of snail and fruits collected from around plantation area. Three different groups of treatment were applied, one group as a control and two groups were treated by additional LMO along vegetative period. The measured parameters were weight of rhizome, curcuminoid and xanthorrhizol levels. The results showed that LMO addition to the regular fertilization able to increase Javanese turmeric productivity and shorten both vegetative and generative period of time while maintain its quality. It can be concluded that LMO application is also good approach for both field, Javanese turmeric agriculture and natural medicine.